PEMANFAATAN LPG SEBAGAI BAHAN BAKAR ALTERNATIF MESIN GENSET PADA KELOMPOK TANI SRI MUMPUNI, DESA DUWET KABUPATEN PEKALONGAN - Dian Arif Rachman; Heri Kiswanto (National Conference for Community Service Project (NaCosPro), 2020)
The human need for food is increasing every day. During the Covid-19 pandemic, disruption of food production is an important matter that must be addressed immediately. One problem that is often faced by farmers as food producers in Indonesia is the problem of drought during the prolonged dry season so that it is threatened with crop failure. Farmers really need this generator modification training because it can reduce the operational costs of rice field irrigation. It is hoped that this service activity can provide new knowledge and help farmers overcome rice fields dryness by using a generator set with LPG fuel.